((The extent of the obligation of the Federal Board of supreme Audit to apply the INTOSAI 3000 standard)) - يحيى صفاء احمد; عبد الله طالب حميد (Journal of Economics and Administrative Sciences, 2025)
Abstract The research aims to demonstrate the commitment of the Federal Financial Supervisory Bureau to meet the requirements of the International Organization of Supreme Audit Institutions (INTOSAI) 3000, the general and private supervision of performance as the highest supervisory authority in Iraq, which is the only authorized to carry out the process of monitoring the performance of government work and activities. To analyze and present the results of the survey questionnaire prepared for the compliance of the Bureau with the requirements of the general and specific criteria related to the performance control process. The researcher reached a number of conclusions, the most important of which is the commitment of the Federal Financial Supervisory Board to meet the requirements of the INTOSAI 3000 standard to a certain extent and this is reflected in the performance of the performance control process. While the most important recommendations were the need to fulfill the requirements of the INTOSAI 3000 standard because it is of direct importance in the implementation of the performance control process carried out by the SAI. The preparation and formulation of standards and control indicators that are consistent with the principles of economy, efficiency and efficiency. SAI for its importance in taking appropriate measures and analyzing the results in a sound and objective manner.